Implementasi Konsep Healing Environment dan Family Centered Care Design pada Interior Pusat Rehabilitasi Kanker untuk Anak-Anak di Surabaya - Crista Putri Prasetio; Ronald Hasudungan Irianto Sitindjak (Intra, 2017)
Cancer is one of the chronic diseases that can affects anyone including children. According to the data of Palliative Development Center and Pain Free department RSUD Dr. Soetomo-Faculty of Medicine Airlangga University, the number of pediatric patients in Surabaya has reached 744 person in 2011 and increases up to 10 until 20 percent annually. Unfortunately, Surabaya does not have any appropriate healthcare facilities which support treatment for children. The problem drives the author to design a better pediatric cancer rehabilitation center in Surabaya in terms of facilities that support psychological treatment as well as a temporary residence for every children along with their family. The facilities will also apply healing environment and family-centered care design that will be realized through the design concepts. Some of the facilities provided are learning facilities, playground and temporary residence. Both of the aspects will works in harmony in the design for pediatric cancer rehabilitation center in Surabaya.